Longitudinal trends with improvement in quality of life after TVT, TVT O and Burch colposuspension procedures - Drahorádová, Petra; Martan, Alois; Švabík, Kamil; Zvára, Karel; Otava, Martin; Mašata, Jaromír (Medical Science Monitor, 2011)
BACKGROUND: Comparison of the quality of life (QoL) trends after TVT, TVT O and Burch colposuspension (BCS) procedures and comparison of long-term subjective and objective outcomes. MATERIAL/METHODS: The study included 215 women who underwent a TVT, TVT O or BCS procedure. We monitored QoL after each procedure and the effect of complications on the QoL as assessed by the IQOL questionnaire over a 3-year period. RESULTS: The study was completed by 74.5% of women after TVT, 74.5% after TVT O, and 65.2% after BCS procedure. In the long-term, the QoL improved from 46.9 to 88.7 and remained stable after BCS; after TVT and TVT O, it declined, but only after TVT O was the decline statistically significant compared to BCS. The IQOL for women with post-operative complications has a clear descending tendency. The effect of the complications is highly significant (p<0.001). Only the OAB complication had a statistically significant effect on QoL p<0.001. Preexistent OAB does not negatively affect postoperative results of anti-incontinence surgery. CONCLUSIONS: There was a statistically significant decline with the longitudinal values of IQOL with TVT O, but not with TVT or BCS. Anti-incontinence operations significantly improve quality of life for women with MI, but compared to the SI group, the quality of life is worse when measured at a longer time interval after the operation. Anti-incontinence operations significantly improve quality of life, and the difference in preoperative status in the long-term follow-up is demonstrable.
Keywords: Suburethral Slings; urologické chirurgické výkony; Urologic Surgical Procedures; lidé; Middle Aged; Adult; pooperační komplikace; Female; průzkumy a dotazníky; Quality of Life; Humans; Postoperative Complications; Urinary Incontinence, Stress; lidé středního věku; suburetrální pásky; stresová inkontinence moči; ženské pohlaví; Aged, 80 and over; senioři nad 80 let; kvalita života; Aged; Postoperative Care; dospělí; Surveys and Questionnaires; pooperační péče; senioři